Peran Guru terhadap Lingkungan Belajar dan Minat Belajar Sains Siswa Kelas II di Sriti Malaysia: The Role of Teachers in the Learning Environment and Science Learning Interest of Grade II Students at Sriti Malaysia - Setiyawati Setiyawati; Rintis Rizkia Pangestika; Muhammad Ferdian Syaifullah (ITScience (Information Technology and Science), 2026)
A conducive learning environment is one of the main factors in building students' interest in learning, especially in Science subjects in elementary schools. This study aims to describe in depth the strategic role of teachers in fostering a conducive learning environment and analyze the impact on the learning interest of second-grade students in Science subjects at SRITI Al-Fateh Malaysia. This study uses a qualitative approach. Data collected through observation, interviews, and documentation are then analyzed using the interactive model developed by Miles, Huberman, and Saldaña, which involves data reduction, data presentation, and data conclusion. The results of the study indicate that teachers play a strategic role in fostering a conducive learning environment by ensuring the classroom is neat, clean, and attractive through educational decorations and exploration corners with a Science theme. In addition, teachers use interactive learning media such as animated videos, simple experiments and giving rewards to increase students' enthusiasm, participation, and curiosity in Science lessons. Thus, the role of teachers in managing a comfortable, creative, and collaborative learning environment is effective in increasing students' interest in learning Science in second grade at SRITI Al-Fateh Malaysia.